Processing sequence for a PureB bipolar junction transistor - Causevic, A.; Funk, H. S.; Schwarz, D.; Guguieva, K.; Schulze, J. (2020 43rd International Convention on Information, Communication and Electronic Technology, MIPRO 2020 - Proceedings, 2020)
Since we have previously shown that the deposition of pure Boron (PureB) on Silicon (Si) forms an almost ideal pn-junction, the next step is to utilize this technology towards a high-speed pnp bipolar junction transistor (BJT) made from Si. Here, the Emitter is made from a PureB. The PureB layer is extremely thin and features an almost defect-free pn-junction, a low off-current and a low series resistance, which makes it feasible to achieve better characteristics than the conventional BJT. However, PureB is very unreactive and therefore hard to etch, which results in a high roughness of the underlying semiconductor after etching. That is why it is challenging to build a three-terminal device such as a BJT. In this work, we present a novel process scheme using a double-layer hardmask of Silicon dioxide (SiO2) and Aluminum oxide (Al2 O3) to enable differential epitaxy of PureB. Onto the substrate a layer stack of SiO2 and Al2 O3 was deposited and structured, the Al2 O3 was then recrystallized to be used as an etch stop. PureB was deposited subsequently by differ-rential epitaxy into the SiO2 windows.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Bipolar junction transistor; Molecular beam epitaxy; Physical vapor deposition; PureB